AUDIT KEAMANAN SISTEM INFORMASI PERPUSTAKAAN: STUDI KASUS DI UNIVERSITAS NAHDLATUL ULAMA AL GHAZALI CILACAP - Eka Tripustikasari; Abednego Dwi Septiadi (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
Nahdlatul Ulama University Al Ghazali Cilacap began to utilize Information and Communication Technology (ICT) to support existing processes so as to produce accurate and fast information. In the implementation of Information and Communication Technology (ICT) governance, information is a very important asset for a company, both information related to management, finance, reports and other information. Leaks, damage, inaccuracies. The aim is to find out the extent of the completeness and maturity of Information Technology at Nahdlatul Ulama Al Ghazali University, Cilacap. However, they do not yet know whether their framework has met the requirements for the level of completeness and maturity of the application of the ISO 27001 standard. For this reason, it is necessary to carry out an information system security audit to determine the current condition compared to the expected condition. In the process, the audit is carried out based on the ISO 27001 Standard which is applied in the form of an evaluation of the KAMI Index. A thorough assessment was carried out on five areas of information security using the US Index version 2.3 template from the Ministry of Communications and Information Technology (Kominfo). The audit results are in the form of recommendations for evaluating the completeness and maturity of the information security framework based on the ISO 27001 standard.